„Święta misja profesora Abronsiusa”. Fantazmaty, abiektalność i transgresje w filmie Romana Polańskiego "Nieustraszeni pogromcy wampirów" - Rawski, Jakub (Załącznik Kulturoznawczy, 2023)
“The Sacred Mission of Professor Abronsius:” Phantasms, The Abject, and Transgression in Roman Polanski’s The Fearless Vampire Killers Roman Polanski’s The Fearless Vampire Killers is usually approached in film and cultural studies from a genological perspective: as a game with the convention and genres, a work that has the features of parody and pastiche, yet complies with the poetics of horror. When interpreting and analyzing the picture, it seems worthwhile to employ phantasmatic criticism drawing on the psychoanalytic theory of culture and consider the issue of the abject and transgressive nature of vampiric heroes. This leads to the exegesis of the film from a poststructuralist perspective with a focus on the existential and sexual aspects of vampirism, a topos analyzed by Maria Janion in terms of being a bloodsucker in the face of death, in the face of sex, and in the face of the tragic human condition. The ontic status of the beast seems to be particularly noteworthy if you consider its evolutionary aspect and the role that Polanski’s film played in this regard.